Disclosure, transparency, and market discipline - Xavier Freixas; Christian Laux (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
The aim of this paper is to examine what has been the role of information provision to the market throughout the crisis. We consider two main sources of information to the market, financial statements and information provided by credit rating agencies. We examine how these sources of information work and the effectiveness of their disclosure process during the crisis. Contrary to the commonly held view, fair value accounting did not have a major impact on the crisis development and severity. However, the structure and lack of accountability of credit rating agencies had a profound impact on their incentives, which may have jeopardized the accuracy of the whole rating process. We claim that the crisis experience has changed the way we think about information as well as market discipline and discuss policy implications and proposals for regulation.
urn:nbn:de:hebis:30-101935
Keywords: G01; G24; G28; M41; M48; 330; Mark-to-Market; Fair-Value Accounting; Credit Rating Agencies; Financial Crisis; Regulation; Financial Institutions; Banks; Finanzmarktkrise; Information; Fair-Value-Bewertung; Publizitätspflicht; Kreditwürdigkeit; Finanzmarkt; Regulierung; Bankenpolitik; Welt